Can ebselen prevent cisplatin-induced ovarian damage? - Soyman, Zeynep; Uzun, Hafize; Bayindir, Nihan; BAYINDIR, NİHAN; EŞREFOĞLU, MUKADDES; EŞREFOĞLU, MUKADDES; Boran, Birtan (My University, 2018)
Purpose The occurrence of ovarian damage is a major shortcoming in treating tumors with cisplatin (CP). The present study investigates the beneficial effects of ebselen-a seleno-organic compound with antioxidant and antiinflammatory properties-vis-a-vis CP-induced ovarian damage.